The Financial Management Practices of the Mosques in the Special Region of Yogyakarta Province, Indonesia - Muhammad Akhyar Adnan (Institute for Research and Community Empowerment (LPPM TAZKIA), 2013)
Objective – This study is trying to investigate the financial management of the Masjid (Mosques) in the Special Region of Yogyakarta Province. Three main issues were focused: the amount of cash flow which include the balances on hand; the application of transparency and accountability principles in financial matters, and sound practice of financial management which include budgeting, strategic formulation and performance evaluation.Methods - The study is an exploratory in nature. The Special Region of Yogyakarta consists of four counties and one city (municipality). 50 Mosques have been selected as the samples. Each county / city is represented by 10 Mosques. They are selected using sampling method. The simple descriptive analysis is conducted on the data collected.Results - Based on the data analysis, the study found that there is a significant cash flow of those selected samples, dominated by Infaq / Sodaqoh. Few Mosques recognized that they also receive Zakah and Waqaf fund.Conclusion - Generally the Mosque Management have applied the principles of transparency and accountability in the form recording, although their skill in doing so needs to be improved. However, a significant number of Mosques Management have not yet set the strategic formulation, as well as budgeting process to realize the budget and its evaluation. Keywords : Cash Flow, Financial Management, Mosque